Força de preensão palmar e resposta metabólica após abreviação do jejum pré-operatório com carboidratos em colecistectomia por laparotomia : estudo randomizado e duplo cego - Gava, Marcella Giovana (2013)
The abbreviation of preoperative fasting for 2 hours with carbohydrate-rich beverage (CHO) is safe. Hand grip strength (DM) is a fast, inexpensive and minimally invasive tool to approach muscle function. AIM: To investigate the effects of the abbreviation of preoperative fasting with oral supplementation containing CHO in the evolution of grip strength (FPP) and in the acute phase inflammatory response in patients who underwent open cholecystectomy. METHODS: A randomized clinical, double-blind trail enrolling adult female patients, aged 18 to 60 years old undergoing open cholecystectomy. Patients were divided into 2 groups: control group, who received a conventional fasting until the time of operation and the intervention group, who received the same fasting for solids but drunk a 12.5% carbohydrate enriched-beverage, six (400 ml) and two (200 ml) hours before the surgical procedure. The handgrip strength was measured at hospital admission (FPPpré), immediately before the operation (FPPim), and postoperatively (FPPpós) in both groups. We collected blood samples preoperatively and postoperatively for serum glucose, insulin, C-reactive protein (PCR) and albumin assays. RESULTS: There were no deaths. The mean (SD) grip strength was significantly higher in at least one hand in the three periods studied: preoperatively in the dominant hand (27,8 (2,6) vs. 24,1 (3,7) kg; p=0,04), at the immediate preoperative period in both hands, and postoperatively in the non-dominant hand (28,5 (3,0) vs. 21,3 (5,9) kg; p=0,01). There was no difference between the two groups for both glucose and insulin, however both levels increased in the two groups (p = 0.01 glucose, insulin p <0.001). We observed an increase in CRP levels (p <0.001) only in the control group (4.0 ± 2.6 to 36.4 ± 17 mg/L, p <0.001) which was greater than the intervention group (p = 0.04). Albumin decreased (p <0.001) in both groups, with no difference between them (p = 0.71). The inflammatory index CRP / albumin ratio increased only in the control group (p <0.01) which was higher when compared with the intervention group (p = 0.03). CONCLUSION: The abbreviation of preoperative fasting for 2 hours with carbohydrate enricheddrinks improves muscle function immediately before the operation and attenuates the postoperative acute-phase response.